2016
DOI: 10.1016/j.jtcvs.2015.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged continuous-flow left ventricular assist device support and posttransplantation outcomes: A new challenge

Abstract: A bridge-to-transplant (BTT) strategy with a CF-LVAD has become standard care for patients with advanced heart failure. Duration of CF-LVAD support is associated with increased midterm mortality, warranting early transplantation in the modern BTT era.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 19 publications
5
41
1
Order By: Relevance
“…Although these data are relatively preliminary, MIS‐VAD patients potentially experience increased survival compared to conventional full sternotomy patients. As mentioned previously, the literature is currently unclear about the long‐term effects of preoperative VAD support in HTx patients . In general, the VAD support time before HTx has been shorter in American patients than in European cohorts in publications to date, and the support duration might have been a relevant factor for these effects .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these data are relatively preliminary, MIS‐VAD patients potentially experience increased survival compared to conventional full sternotomy patients. As mentioned previously, the literature is currently unclear about the long‐term effects of preoperative VAD support in HTx patients . In general, the VAD support time before HTx has been shorter in American patients than in European cohorts in publications to date, and the support duration might have been a relevant factor for these effects .…”
Section: Discussionmentioning
confidence: 99%
“…As a result, an increasing number of patients with VADs are undergoing transplantation . Current data are still unclear whether former VAD support, especially with a prolonged support time, may impair the outcome after HTx . Whereas data from the International Thoracic Organ Transplant Registry of the International Society of Heart and Lung Transplant showed no significant differences between patients undergoing primary HTx and patients with implanted VADs undergoing HTx, Rizwan et al reported a worse outcome for a large cohort of young adults who received a bridge treatment with a VAD.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the bridge-to-transplant (BTT) strategy with continuous-flow ventricular assist devices (CF-LVADs) has played a major role in providing temporary support for adult patients with end-stage heart failure. 1 Additionally, venoarterial extracorporeal membrane oxygenation (ECMO) use as a rescue therapy in the setting of acute cardiac failure has also been increasing in recent years, 2,3 whereas use of ECMO as a direct bridge to transplantation in adult populations is extremely infrequent worldwide, particularly in the United States. 4 Each adult heart transplant candidate at time of registration is assigned a status that reflects his or her medical urgency for transplant.…”
Section: See Editorial Commentary Page 1619mentioning
confidence: 99%
“…The scarcity of donors has led to the generation of a whole field of mechanical circulatory support devices which has brought in a new era in the treatment of advanced heart failure. The use of continuous flow LVADs as a bridge to transplantation (BTT) has become more popular and the mainstay of patients waiting on the transplant list [32]. More recently, VA-ECMO is being increasingly used as a rescue therapy [33,34] However, this trend has now led to the use of ECMO as a direct bridge to transplantation in adults.…”
Section: Ecmo As a Bridge To Transplantationmentioning
confidence: 99%